Chronic kidney disease and its associated factors in HIV-infected individuals: a comparison of antiretroviral therapy naïve and experienced patients - Asmelash, Daniel; Nigatie, Marye (Frontiers in Medicine, 2024)
Background: Chronic kidney disease has emerged as one of the primary co-morbid conditions affecting human immunodeficiency virus infected individuals even after highly-active antiretroviral therapy. The main objective of this study was to assess chronic kidney disease and associated factors among highly active antiretroviral therapy naïve and experienced HIV infected individuals.: An institution based cross-sectional study was conducted at the Mizan Tepi University comprehensive specialized Hospital from March to May 2022. Double population proportion formula wasere used to select 250 study participants and from 250 study participantsof these, 125 were highly active antiretroviral therapy naïve and 125 were experienced. Socio-demographic and clinical data were collected by using semi-structured questionnaire. A serum creatinine level was measured using Mindray BS-200 chemistry analyzer and estimated glomerular filtration rate (eGFR) was calculated using the Modification of Diet in Renal Disease (MDRD) equation. The level of urine protein measured by using reagent strip within 30 minutes. Descriptive statistics, independent t-test, and multivariable logistic regression analysis were performed. A P-value of <0.05 was considered as statistically significant.The mean (±SD) age of the HAART naïve and experienced individuals wasere 35±9.5 and 45±9.9 years, respectively. Of the total, 67.2% were females. The overall prevalence of CKD among HIV infected study participants was 36.4%. The prevalence of CKD in HAART naïve and HAART-experienced individuals was 33.6%and 39.2%. respectively with p-value 0.03. Male gender was independently associated with chronic kidney disease in this study. wasThe prevalence of CKD was higher among HAART-experienced than HAART naïve HIV infected individuals. A renal function assessment should be done before and during HAART to reduce renal dysfunction.